Children's Learning Motivation in Rural Area of Bandung - Dinar Setiawan (Universitas Pendidikan Indonesia, 2023)
Background: the development of learning motivation in pre-school children is something that should be paid attention to at this time, children's learning motivation at this age will have a major impact on learning achievement in the future. Purpose: To find out the description of children's learning motivation in Permata Bunda Kindergarten, Sindang Panon Village, Banjaran District, Bandung Regency. Methods: This research is a quantitative descriptive study with a cross sectional approach. The subjects of this study amounted to 70 people who were determined through the total sampling technique. Collecting data on learning motivation used observation sheets. Results: most of the respondents 60 (85.7%) have high learning motivation. The conclusion of the results of this study can be input for teaching staff to optimize the high motivational potential of students for optimal cognitive development.